SPATIAL PATTERN OF HOUSEHOLD TRAVEL IN MINNA METROPOLIS, NIGERIA - Ademola, Ojekunle Joel; Samuel, Owoeye Adelanke (International Journal of Research -GRANTHAALAYAH, 2018)
Household travel is the major origin of traffic flow in the urban centres. Urban residents travel for various purposes; planning and managing urban travel requires that city planners and managers understand their flow pattern across the city space. This study therefore, was conducted to analyse the spatial pattern of household travel in Minna City, Nigeria. The data were collected through questionnaire administration on 1,303 respondents using Open Data Kit (ODK) package. To do this, the city was divided into four cluster zones, from which three different residential densities were selected in each of the zones. The study reveals that trip generation and attraction is significantly different among different residential densities in the city. The analysis of variance reveals there is significant difference in trip distances covered by different residential area in the city with a p-value of <0.001. The study therefore recommends that there is need to create spatial balance in the location of services needed and land use activities across the residential densities and also provide an effective and efficient public transportation system to the city residents especially along the main traffic corridors.